p38MAPK Signaling Pathway in Osteoarthritis: Pathological and Therapeutic Aspects - Li Z; Dai A; Yang M; Chen S; Deng Z; Li L (Dove Medical Press, 2022)
Zongchao Li,1 Aonan Dai,1 Ming Yang,1 Siyu Chen,2,3 Zhenhan Deng,2,3,* Liangjun Li1,* 1Department of Orthopaedics, The Affiliated Changsha Central Hospital, Hengyang Medical School, University of South China, Changsha, People's Republic of China; 2Department of Sports Medicine, The First Affiliated Hospital of Shenzhen University, Shenzhen Second People's Hospital, Shenzhen, People's Republic of China; 3School of Clinical Medicine, Guangxi University of Chinese Medicine, Nanning, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhenhan DengDepartment of Sports Medicine, The First Affiliated Hospital of Shenzhen University, Shenzhen Second People's Hospital, 3002 Sungang West Road, Shenzhen City, 518035, People's Republic of China, Tel +86 13928440786, Fax +86 755-83366388, Email dengzhenhan@email.szu.edu.cn; Liangjun LiDepartment of Orthopaedics, The Affiliated Changsha Central Hospital, Hengyang Medical School, University of South China, 161 Shaoshan South Road, Changsha City, 410018, People's Republic of China, Tel +86 13875822004, Fax +86 731-85668156, Email lilianngjun1212@sina.comAbstract: Osteoarthritis (OA) is an aging-related joint disease, pathologically featured with degenerated articular cartilage and deformation of subchondral bone. OA has become the fourth major cause of disability in the world, imposing a huge economic burden. At present, the pathogenesis and pathophysiology of OA are still unclear. Complex regulating networks containing different biochemical signaling pathways are involved in OA pathogenesis and progression. The p38MAPK signaling pathway is a member of the MAPK signaling pathway family, which participates in the induction of cellular senescence, the differentiation of chondrocytes, the synthesis of matrix metalloproteinase (MMPs) and the production of pro-inflammatory factors. In recent years, studies on the regulating role of p38MAPK signaling pathway and the application of its inhibitors have attracted growing attention, with an increasing number of in vivo and in vitro studies. One interesting finding is that the inhibition of p38MAPK could suppress chondrocyte inflammation and ameliorate OA, indicating its therapeutic role in OA treatment. Based on this, we reviewed the mechanisms of p38MAPK signaling pathway in the pathogenesis of OA, hoping to provide new ideas for future research and OA treatment.Keywords: osteoarthritis, p38MAPK signaling pathway, aging, inflammation